Safety nets for improved tilapia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
With more farmers adopting aquaculture as an option for improving food production and farm income, scientists are looking at ways to raise productivity through genetic improvement. This carries a number of risks, principally in terms of the fish...